The mediating role of neuroticism and anxiety sensitivity in the relationship between childhood trauma and panic disorder severity - He, Fang; Yang, Xiangyun; Luo, Jia; Wang, Pengchong; Yang, Lijuan; Li, Zhanjiang (Frontiers in Psychiatry, 2024)
Objective: Despite advancements in understanding panic disorder (PD), its etiology and pathogenesis remain elusive, particularly concerning the influence of psychosocial factors. This study aims to explore the mediating roles of neuroticism and anxiety sensitivity (AS) in the relationship between childhood trauma and PD severity.Methods: We conducted a cross-sectional analysis involving 84 individuals diagnosed with PD and 112 age-and gender-matched healthy controls (HC). Childhood trauma was assessed using the validated Childhood Trauma Questionnaire (CTQ), while anxiety sensitivity levels were measured using the Anxiety Sensitivity Index-3 (ASI-3). Neuroticism was evaluated using the Chinese Big Five Personality Inventory (CBF-PI-B). The severity of PD was determined using the Panic Disorder Severity Scale (PDSS). Statistical analysis encompassed both correlation and mediation techniques to thoroughly examine the relationships among childhood trauma, neuroticism, AS, and PD severity.Results: Individuals with PD exhibited significantly higher CTQ, ASI-3, and neuroticism scores compared to HC (all P<0.05). Within the PD group, strong positive correlations were found between CTQ scores, ASI-3 scores, neuroticism levels, and PDSS scores, with correlation coefficients ranging from 0.336 to 0.504 (all P<0.001). Additionally, our results indicated that neuroticism and AS acted as mediating factors in the relationship between childhood trauma and the severity of PD, with the 95% confidence interval for the indirect effects ranging from 0.028 to 0.116.This study highlights that PD patients exhibit significantly higher levels of childhood trauma, neuroticism, and AS compared to HC. Furthermore, childhood trauma indirectly influences PD severity through a chain mediation involving neuroticism and AS. These findings suggest the importance of psychological factors in moderating the impact of early adverse experiences on the development and progression of PD.